Characterization of Slow and Fast Fading in Off-Body Communication at 2.45 GHz with Space Diversity Scheme in an Indoor Environment - Szymon Wiszniewski; Slawomir J. Ambroziak (International Journal of Antennas and Propagation)
The characterization of slow and fast fading in wireless body area networks with space diversity scheme has been presented. The analysis, based on the measurements at 2.45 GHz in an indoor environment, has shown that for all investigated configurations of receiving wearable antennas, the correlation coefficient values of the received signals’ parameters are below the assumed value of 0.5, being close to zero for the vast majority of cases. It has been shown that the slow fading component may be modelled by a lognormal distribution with zero average and the standard deviation from the range of [1.43, 1.98] dB. The fast fading component is the best modelled by a Rice distribution with the noncentrality parameter and the scale parameter being in the range [0.8125, 0.9624] and [0.5269, 0.6954], respectively.